IMPLEMENTATION OF PRESIDENTIAL REGULATION NO. 35 OF 2018 IN MANAGING WASTE INTO ELECTRICAL ENERGY: A CASE STUDY OF TANGERANG CITY AS A NATIONAL STRATEGIC PROJECT - Candra, Edi; Sartika, Ika (Justisi: Jurnal Ilmu Hukum, 2025)
This study aims to analyze the implementation of Presidential Regulation (Perpres) No. 35 of 2018 on the Acceleration of Waste-to-Energy Plant Development Using Environmentally Friendly Technology in Tangerang City, designated as one of the national strategic projects. This regulation is introduced as a solution to the escalating urban waste management issues and as a means to meet the demand for renewable energy. The study focuses on evaluating the policy's execution, covering infrastructure readiness, local government support, and private sector involvement in transforming waste into electrical energy. Employing a qualitative approach, this research collects data from in-depth interviews with stakeholders, field observations, and analysis of related documents. The findings indicate that while the policy has driven significant progress in waste management and renewable energy creation, several challenges persist, such as technical constraints in processing, limited public understanding of the program, and a need for stricter operational regulations. The study concludes that achieving full success in this program requires synergy between the government, community, and private sectors, as well as regulatory strengthening for waste-to-energy management. These findings are expected to serve as a reference in advancing sustainable waste management policies in Indonesia